Role of (18)F-fluoro-2-deoxyglucose Positron Emission Tomography in Gastric GIST: Predicting Malignant Potential Pre-operatively - Park, Jeon-Woo (The Korean Gastric Cancer Association, 2011)
PURPOSE: It is difficult to obtain biopsies from gastrointestinal stromal tumors (GISTs) prior to surgery because GISTs are submucoal tumors, despite being the most common nonepithelial neoplasms of the gastrointestinal tract. Unlike anatomic imaging techniques, PET-CT, which is a molecular imaging tool, can be a useful technique for assessing tumor activity and predicting the malignant potential of certain tumors. Thus, we aimed to evaluate the usefulness of PET-CT as a pre-operative prognostic factor for GISTs by analyzing the correlation between the existing post-operative prognostic factors and the maximum SUV uptake (SUVmax) of pre-operative 18F-fluoro-2-deoxyglucose (FDG) PET-CT. MATERIALS AND METHODS: The study was conducted on 26 patients who were diagnosed with gastric GISTs and underwent surgery after being examined with pre-operative FDG PET-CT. An analysis of the correlation bewteen (i) NIH risk classfication and the Ki-67 proliferation index, which are post-operative prognostic factors, and (ii) the SUVmax of PET-CT, which is a pre-operative prognostic factor, was performed. RESULTS: There were significant correlations between (i) SUVmax and (ii) Ki-67 index, tumor size, mitotic count, and NIH risk group (r=0.854, 0.888, 0.791, and 0.756, respectively). The optimal cut-off value for SUVmax was 3.94 between "low-risk malignancy" and "high-risk malignancy" groups. The sensitivity and specificity of SUVmax for predicting the risk of malignancy were 85.7% and 94.7%, respectively. CONCLUSIONS: The SUVmax of PET-CT is associated with Ki-67 index, tumor size, mitotic count, and NIH classification. Therefore, it is believed that PET-CT is a relatively safe, non-invasive diagnostic tool for assessing malignant potential pre-operatively.